Kangaroo mother care knowledge and practice among mothers who gave birth to preterm and low birth weight babies in Amhara regional state referral hospitals, North West Ethiopia - Bitewsh Azmeraw Getie; Ayenew Engida Yismaw; Agumas Eskezia Tiguh (Elsevier, 2022)
Background: Kangaroo mother care is skin-to-skin contact between the mother and neonate, and is done with the mother's chest. It decreases neonatal morbidity and mortality by preventing hypothermia and infection in low-birth weight neonates. For effective implementation of kangaroo mother care services, the mother's active participation is crucial. However, there is limited evidence on mothers' knowledge and practice in this regard in Ethiopia. Therefore, this study aimed to assess Kangaroo mother care knowledge and practice among mothers who gave birth to preterm and low birth weight babies in Amhara regional state referral hospitals, northwest Ethiopia. Methods: An institutional based cross-sectional study was conducted among 620 mothers from February to April 2021, with a multi-stage sampling method. Interviews, record reviews, and observations were used to collect data. Epi Data version 4.6 was used to enter data, and SPSS version 25 was used to analyze it. Logistic regression analysis was conceded. Statistically significant associations between variables were determined based on the adjusted odds ratio with a 95% confidence interval and a p-value < 0.05. Results: Good knowledge and practice of kangaroo mother's care by mothers were 56.9% and 41.3%, respectively. Having a college or higher level of education (AOR; 6.1; 95% CI: 1.9, 12.0) and (AOR; 2.3; 95% CI: 1.8, 6.17), having family support (AOR; 3.6; 95% CI: 2.2, 5.8) and (AOR; 2.2; 95% CI: 1.4, 3.5), having kangaroo mother care private space (AOR; 1.97; 95% CI: 1.3, 2.9) and (AOR; 1.5;95% CI:1.05,2.5) were significant variables with both knowledge and practice of mother's kangaroo mother care respectively. Urban residency (AOR; 3.6; 95% CI: 2.1, 6.1) and having antenatal care follow-up (AOR; 8; 95% CI: 3.1, 15) showed an association with knowledge of kangaroo mother care. Hospital delivery (AOR; 2.4; 95% CI: 1.4-8.9) had a significant association with good practice of kangaroo mother care. Conclusion and recommendation: Mothers' good knowledge and good practices of kangaroo mother care were low. Thus, encouraging women to have better academic attainment and spacing separate Kangaroo mother care corners at hospitals may enhance mothers' knowledge and practice of Kangaroo mother care.